Effectiveness of eHealth-Based Psychological Interventions for Depression Treatment in Patients With Type 1 or Type 2 Diabetes Mellitus: A Systematic Review - Varela-Moreno, Esperanza; Carreira Soler, Mónica; Guzmán-Parra, José; Jódar-Sánchez, Francisco; Mayoral-Cleries, Fermín; Anarte-Ortíz, María Teresa (Frontiers in Psychology, 2022)
Background: Comorbidity between diabetes mellitus and depression is highly prevalent. The risk of depression in a person with diabetes is approximately twice that of a person without this disease. Depression has a major impact on patient well-being and control of diabetes. However, despite the availability of effective and specific therapeutic interventions for the treatment of depression in people with diabetes, 50% of patients do not receive psychological treatment due to insufficient and difficult accessibility to psychological therapies in health systems. The use of information and communication technologies (ICTs) has therefore been proposed as a useful tool for the delivery of psychological interventions, but it continues to be a field in which scientific evidence is recent and controversial. This systematic review aims to update the available information on the efficacy of psychological interventions delivered through ICTs to improve depressive symptomatology in patients with diabetes. Methods: A systematic review of the literature was performed following the PRISMA guidelines and using multiple databases. Inclusion criteria included randomized clinical trials of eHealth treatments for patients with diabetes and comorbid depression from 1995 through 2020. Results: The initial search identified 427 relevant scientific publications. After removing duplicates and ineligible citations, a total of 201 were analyzed in full text. Only ten studies met the inclusion criteria established in the protocol registered in PROSPERO for this systematic review. Conclusions: ICT-based psychological interventions for the treatment of depression in people with diabetes appear to be effective in reducing depressive symptomatology but do not appear to provide significant results with regard to glycemic control. Nonetheless, the scientific evidence reported to date is still very limited and the methodology very diverse. In addition, no studies have implemented these systems in routine clinical practice, and no studies are available on the economic analysis of these interventions.